Pendapatan Rumah Tangga Transitif dan Pertumbuhan Sosial Ekonomi di Kecamatan Kauditann - Mangowal, Benny (JBE (Journal of Business and Economics); Volume 9 No.2, 2010 JBE UNKLAB, 2010)
Household income, in terms of transitive income was assumed related to the phenomenon of social-economic growth in Kauditann county. There growth variables were analyzed as dependent, significant relationship to the six variables of households. Residence was considered a dependent variable, significantly related to the six variables of households. The six variables were correlated and tested in matrix correlation then conmed overall with anova and regression analysis. Transportation, gave another significant relation to the same variable, as well as social welfare (at alpha 0.05%).